Extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) infections: are carbapenem alternatives achievable in daily practice?. (October 2015) - Pilmis, B.; Delory, T.; Groh, M.; Weiss, E.; Emirian, A.; Lecuyer, H.; Lesprit, P.; Zahar, J.-R.
Highlights: De-escalation after empirical treatment with a carbapenem is rarely done. Escherichia coli -related infection was found to be a protective factor against carbapenem prescription. There was no difference in mortality between the de-escalation and no de-escalation groups. Recurrence of infection was the most frequent reason for no de-escalation. Summary: Objectives: To avoid the use of carbapenems, alternatives such as cephamycin, piperacillin–tazobactam, and others are suggested for the treatment of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) infections. The aim of this study was to evaluate the frequency and the feasibility of antimicrobial de-escalation for ESBL-PE-related infections. Methods: A prospective observational, bi centric cohort study was conducted. All patients with ESBL-PE infections were included. De-escalation was systematically suggested if patients were clinically stable and the isolate was susceptible to possible alternatives. Results: Seventy-nine patients were included: 36 (45.6%) were children, 27 (34.1%) were hospitalized in intensive care units, and 37 (47%) were immunocompromised. Urinary tract infections, pneumonia, and catheter-related bloodstream infections accounted for 45.6%, 19%, and 10%, respectively, of the cohort. Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae were the three most frequent causative organisms isolated. On day 5, 47 (59.2%) of the patients were still receiving carbapenems. Antimicrobial resistance (44.7%), infection relapse (26.9%), and clinical instability (19.2%) were the most important reasons for not prescribing alternatives. E. coli- related infections appeared to be a protective factor against maintaining the carbapenem prescription (odds ratio 0.11, 95% confidence interval 0.041–0.324; p = 0.0013). Conclusions: In clinical practice, less than 50% of patients with ESBL-PE-related infections were de-escalated after empirical treatment with carbapenems.